2019
DOI: 10.1021/acsami.9b03884
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Carrier Kinetics in Perovskite Solar Cells

Abstract: Hybrid organic-inorganic halide perovskite solar cells have emerged as leading candidates for third-generation photovoltaic technology. Despite the rapid improvement in power conversion efficiency (PCE) for perovskite solar cells in recent years, the low frequency carrier kinetics that underlie practical roadblocks such as hysteresis and degradation remain relatively poorly understood. In an effort to bridge this knowledge gap, we perform here correlated low frequency noise (LFN) and impedance spectroscopy (IS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…The raise of capacitance at low frequency has been interpreted in many cases as the manifestation of bulk traps. However a recent study 35 using the analysis of low frequency noise has found that the capacitance does not scale with thickness, in agreement with the previous scaling properties obtained by impedance spectroscopy. 36 Figure 4.…”
Section: Ionic Effects At the Interfacesupporting
confidence: 85%
“…The raise of capacitance at low frequency has been interpreted in many cases as the manifestation of bulk traps. However a recent study 35 using the analysis of low frequency noise has found that the capacitance does not scale with thickness, in agreement with the previous scaling properties obtained by impedance spectroscopy. 36 Figure 4.…”
Section: Ionic Effects At the Interfacesupporting
confidence: 85%
“…Considering the time span of the experiments, the OCVD measurements have little to do with the degradations of the cells; rather, they indicate the effect is also clearly evident in the low frequency capacitance measurements. In this line, frequency dependent capacitance measurements under dark portray a significant change in the electrode polarization [29][30][31] as shown in Fig. S9 in the supplementary material.…”
Section: ) and S8(b)mentioning
confidence: 74%
“…The investigation of fluctuation phenomena, which may be called "fluctuation spectroscopy", is a very informative method for the study of kinetic processes in matter. It is often also a method that is much more sensitive than the measurement of average quantities, as demonstrated in superconducting thin films [31][32][33][34] and devices [35][36][37][38], in low-dimensional conductors [39][40][41][42], in carbon nanotubes [43][44][45][46][47] and magnetic composites [48,49], and in conventional [50,51] and innovative solar cells [52][53][54][55]. The role of the noise spectrum analyzer is similar to the role of a microscope: It enables us to visualize the microscopic motion and transitions of particles.…”
Section: Introductionmentioning
confidence: 99%